2021
DOI: 10.1007/s00405-021-06958-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on the incidence of otitis media with effusion in adults and children: a multicenter study

Abstract: Purpose To compare and analyze the incidence of otitis media with effusion (OME), before and during the COVID-19-related pandemic period, to evaluate the effects of the social changes (lockdown, continuous use of facial masks, social distancing, reduction of social activities) in the OME incidence in children and adults. Methods The number of diagnosed OME in e five referral centers, between 1 March 2018 and 1 March 2021, has been reviewed and collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Previous studies in other countries have reported a similar trend in childhood OM incidence during the first COVID-19 peak ( Hatoun et al., 2020 ; Aldè et al., 2021 ; Angoulvant et al., 2021 ; Iannella et al., 2021 ; Torretta et al., 2021 ). Under normal circumstances, OM typically shows a seasonal pattern with a winter peak coinciding with the increase in URTI incidence ( Castagno and Lavinsky, 2002 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies in other countries have reported a similar trend in childhood OM incidence during the first COVID-19 peak ( Hatoun et al., 2020 ; Aldè et al., 2021 ; Angoulvant et al., 2021 ; Iannella et al., 2021 ; Torretta et al., 2021 ). Under normal circumstances, OM typically shows a seasonal pattern with a winter peak coinciding with the increase in URTI incidence ( Castagno and Lavinsky, 2002 ).…”
Section: Discussionsupporting
confidence: 72%
“…CSOM is characterized by chronic inflammation of the middle ear and mastoid mucosa together with a non-intact tympanic membrane and persisting ear discharge ( Verhoeff et al., 2006 ). Several reports from the early phase of the COVID-19 pandemic have suggested a decline in doctor consultations for OM in children ( Hatoun et al., 2020 ; Aldè et al., 2021 ; Angoulvant et al., 2021 ; Iannella et al., 2021 ; Kaur et al., 2021 ; Torretta et al., 2021 ; van de Pol et al., 2021 ). The question is whether the infection control measures or the sudden COVID-19 related changes in health care access and delivery are responsible for these changes.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al (Japan) reported that tonsillitis cases in children under the age of 15 decreased by 29.3% in this period (18). We also found a decrease of 54.01% in the prevalence of acute otitis media, similar to a multi-centre study in Italy, in which Iannella et al (19) concluded that otitis media decreased by 68.1% between March 2020 and March 2021 with respect to the same period of the previous year. In the Netherlands, primary care diagnoses of acute otitis media decreased by 63% between March 2020 and February 2021, compared to the same period the previous year (20).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a large multicenter study reported a lower incidence of otitis media with effusion during the pandemic period, in comparison with the two previous non pandemic years [19] . In addition, recent studies demonstrated a decrease in Pediatric Emergency Department attendance during the Italian lockdown, which was particularly relevant when diagnoses as middle ear disease, and non-complicated middle ear infection were considered [20] . A similar decreasing incidence of otitis media with effusion during the lockdown period has also been observed by several authors worldwide in the last years [21] , [22] , [23] , [24] , thus supporting the clinical influence of social distancing and a reduced school attendance especially for young children.…”
Section: Discussionmentioning
confidence: 98%